If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2t + 75 = 29 Reorder the terms: 75 + -2t = 29 Solving 75 + -2t = 29 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-75' to each side of the equation. 75 + -75 + -2t = 29 + -75 Combine like terms: 75 + -75 = 0 0 + -2t = 29 + -75 -2t = 29 + -75 Combine like terms: 29 + -75 = -46 -2t = -46 Divide each side by '-2'. t = 23 Simplifying t = 23
| 2x^4-28x^2-90=0 | | -3(6p+4)= | | 9+3x+4x=58 | | 2/7x-6=9/7x | | 3y-7=24 | | 2x-6x+3x-6+4x= | | 2X^2-32X-128=0 | | 32.50/5 | | 1x+4/3=10/6 | | 3y-7=16 | | 1.2=2.4+0.6x | | 4g-5-9-4g= | | -100=-4 | | 100-200=a | | 5y-6+2y=4+7y+2 | | y=1907(40) | | 4x+3+7x=16x-1 | | -9x-23=3 | | 6m+8=14+3m | | 2(5c-1)-6=6c+4 | | p=2*26+2*137 | | 5w+24+2w+13=156 | | 3-(-9+3i)-(2-i)= | | 4+x+11=12x-5 | | -6y-8=-5y-9 | | -7m-8=-9m+6 | | 3x(2x-1)=-75 | | 8+6x=-4 | | 4(3a-2)=16 | | 20x-2=28+4 | | 7-c=36 | | 4(2x+7)=-7+27 |